Makam Tradisional Etnis Cina di Kota Ambon - Cheviano E. Alputila (Balai Arkeologi Maluku, 2014)
Ethnic Chinese have a long history around the world. As a people renowned for their versatility in the trade, this community can be found anywhere. Ambon city is one of the many areas in the past inhabited by the ethnic Chinese community. Evidence of their existence in the past in Ambon today can be observed from traditional Chinese tombs are scattered in several locations. In addition to functioning as an initial step in the record of its existence this paper serves to reveal the importance of the existence of traditional Chinese tomb in the city of Ambon. The method used is a survey, interviews, and literature review. From the survey results it is known that the traditional Chinese grave condition as a whole in the city of Ambon was on the verge of collapse and require serious attention of all parties. Loyalty to the ancestral customs of the people of China still run by the Chinese community in the city of Ambon. This is reflected in the traditional Chinese tomb suitability components in common with traditional Chinese tomb in the city of Ambon.Etnis Cina memiliki sejarah yang panjang di seluruh dunia. Sebagai orang-orang yang terkenal karena kepandaiannya dalam berdagang, komunitas ini dapat ditemukan dimana saja. Kota Ambon adalah satu dari sekian banyak daerah yang pada masa lalu didiami oleh masyarakat Etnis Cina. Bukti keberadaan mereka pada masa lalu di Ambon saat ini dapat diamati dari makam-makam tradisional Cina yang tersebar di beberapa lokasi. Selain berfungsi sebagai langkah awal dalam mendata keberadaannya tulisan ini berfungsi untuk mengungkap nilai penting keberadaan makam tradisional Cina di Kota Ambon. Metode yang digunakan yaitu survei, wawancara, dan penelusuran pustaka. Dari hasil survei diketahui bahwa kondisi makam tradisional Cina secara keseluruhan di Kota Ambon berada di ambang kehancuran dan membutuhkan perhatian serius dari semua pihak. Kesetiaan terhadap adat istiadat leluhur Cina tetap dijalankan oleh masyarakat komunitas Tionghoa di Kota Ambon. Hal ini tercermin dari kesesuaian komponen makam tradisional Cina secara umum dengan makam tradisional Cina di Kota Ambon.